TINJAUAN TENTANG MUTU TERPADU - Ramli, Hj. Efni (AL-ISHLAH: Jurnal Pendidikan, 2015)
Integrated Quality Management (TQM) is a management system focuses on a group of people aiming at an increase in satisfying customers with lower costs continuously. Integrated Quality is an integrated system approach (not a separate area or program), and an integral part of the strategy high.In the level of total quality perspective, the educational managers should be held that: (1) Everyone involved in education is a part of the educational process. (2) All the education process should be supervised,  because it required the presence of inspectors. (3) The education managers must also control the functioning of self sebagain any educational process. The process involves the design of education, process control by education providers, and managers of education must involve all parties to get their commitment in the design, re-design and control of the educational process in order to remain productive